Study of the Combined Effect of Ammonia Addition and Air Coflow Velocity on a Non-premixed Methane Jet Flame Stabilization - Colson, Sophie; Kuhni, Manuel; Galizzi, Cédric; Escudié, Dany; Kobayashi, Hideaki (Combustion Science and Technology, 2022)
Ammonia is a promising carbon-free fuel that can be used for CO 2 reduction. However, ammonia industrial use presents challenges, including flame stabilization. In this study, a non-premixed methane-ammonia jet flame in an air coflow was considered to observe the effects of ammonia addition on conventional fuels flame stabilization. First, the effects of the introduction of ammonia on the stabilization regimes of the methane jet flame were studied. Then the coupled effects of the variation in ammonia concentration and air coflow velocity on flame stabilization were investigated. In the present jet configuration, a sharp reduction of the stabilization domain was observed with ammonia addition: the liftoff and re-attachment velocities were obtained for mixtures of up to 50% of ammonia in the fuel, a ratio above which the flame could not be stabilized. When increasing the coflow velocity, a sudden drop in the re-attachment velocity occurred for methane/ammonia flames. This re-attachment drop was associated with an increase in the height of the lifted flame when the jet velocity decreases before re-attachment, for large enough coflow velocity and ammonia concentration. A critical height above which the lifted flames all present the same ascending behavior could be defined and characterizes this peculiar phenomenon.